Analisis Dilema Etika Dalam Profesi Akuntan Publik (Studi Kasus Pada Kantor Akuntan Publik Heru Satria Rukmana 2022-2024: (Case Study at Public Accounting Firm Heru Satria Rukmana 2022-2024) - Wahjuny Djamaa; Annisa Annisa; Rizal Bakti; Heirunissa Heirunissa; Rio Eldianson (Journal Of Business, Finance, and Economics (JBFE), 2025)
This study aims to analyze the ethical dilemmas faced by public accountants in the implementation of financial statement audits at the Public Accounting Firm Heru Satria Rukmana for the 2022-2024 period. This research uses a descriptive method with a qualitative approach through interviews with three parties, namely public accountants, clients, and audit managers. The results of the study show that public accountants in this office often experience ethical dilemmas in the form of pressure from clients to adjust audit results according to the interests of management. Despite this, the majority of accountants still adhere to the applicable professional code of ethics and auditing standards. Clients rated the auditor as having good integrity and independence, although some clients admitted to having tried to put pressure on the auditor. On the other hand, audit managers have an important role in handling dilemmatic situations and maintaining the implementation of the code of ethics in the office environment. Overall, Public Accounting Firm Heru Satria Rukmana has made efforts to implement professional ethical standards well, although challenges from external pressures are still the main obstacles that need to be anticipated. This research is expected to be a reference for the public accounting profession in facing ethical dilemmas and maintaining professionalism and integrity in the implementation of duties.